Bank Lending : Principles and practice. - Lee, Nirmala; Lee, Vijay (Reading : Gosbrook Professional Publishing Ltd, 2018)
This book is for students and professionals working, or intending to work, in a lending-related role. It provides comprehensive, up-to-date coverage of bank lending and will give lending staff the detailed knowledge and understanding of the financial and legal aspects of their roles they need to fulfil employer, as well as customer, expectations.
12.1 THE ECONOMIC AND SOCIAL EFFECTS OF LENDING12.2 RESPONSIBLE LENDING; 12.3 RELATIONSHIP LENDING AND RESPONSIBLE LENDING; 12.4 CONCLUSION; Appendix A: Suggested answers to case study questions; Table of cases; Table of statutes; Table of statutory instruments; Table of European legislation; References; Index; Back Cover.
Print version record.
eBooks on EBSCOhost
Keywords: Bank loans; Prêts bancaires; BUSINESS & ECONOMICS -- Finance; Bank loans